Self-regulated learning in IT-integrated learning environment: its relationships with information literacy and attitudes towards IT - Ng, Melissa Lee Yen; Abu Bakar, Kamariah; Wong, Su Luan; Roslan, Samsilah (Universiti Putra Malaysia Press, 2008)
Self-regulated learning is a vital skill in IT-integrated learning environment. Its importance becomes evident after the explosion of Information Technology (IT). There is now substantial body of research showing that learning in IT-integrated environment is an active, and constructive process. It may be related to the learner’s self-attribute such as their information literacy and attitudes towards IT. This study aims to examine the relationships between self-regulated learning, information literacy and attitudes towards IT among smart school students. Self-regulated learning was gauged by the Motivated Strategies for Learning Questionnaire (MSLQ) while attitudes towards IT were measured with the Attitudes towards IT Scale. An Information Literacy Scale was built specifically to measure students’ information literacy. Its validity and reliability were established in this study. A total of 322 students from two randomly chosen smart schools were sampled. Findings revealed that students’ self-regulated learning was positively and significantly related to their information literacy (r=.42, p<.01) and attitudes towards IT (r=.37, p<.01). Further analyses on specific self-regulated learning strategies suggest that students’ information literacy is more related to their usage of cognitive and metacognitive strategies, while attitudes towards IT is more related to the use of resource management strategies.